Oseltamivir Enhances Hippocampal Network Synchronization - Atsushi Usami; Takuya Sasaki; Nobuhiro Satoh; Takahiro Akiba; Satoshi Yokoshima; Tohru Fukuyama; Kenzo Yamatsugu; Motomu Kanai; Masakatsu Shibasaki; Norio Matsuki; Yuji Ikegaya (Journal of Pharmacological Sciences, 2008)
Oseltamivir, a widely used anti-influenza drug, inhibits virus neuraminidase. A mammalian homologue of this enzyme is expressed in the brain, yet the effect of oseltamivir on central neurons is largely unknown. Patch-clamp recordings ex vivo revealed that oseltamivir enhanced spike synchronization between hippocampal CA3 pyramidal cells. Time-lapse multineuron calcium imaging revealed that oseltamivir and its active metabolite evoked synchronized population bursts that recruited virtually all neurons in the network. This unique, so-far-unknown, event was attenuated by muscarinic receptor antagonist. Thus, oseltamivir is a useful tool for investigating a new aspect of neural circuit operation.Supplementary Fig. and movie: available only at http://dx.doi.org/10.1254/jphs.SC0070467 Keywords:: oseltamivir, functional multineuron calcium imaging, network excitability